Analysis of the Streak Feature in Forming Phatic Communication in Generation Z’s Interactions on the TikTok Platform - Zefanya Sortaria Simanjuntak; Syafrida Nurrachmi Febriyanti (Lavish Opulent Education, 2025)
This study aims to describe and understand the meaning of the streak phenomenon on TikTok as a form of digital social communication practice among Generation Z. The streak reflects how Gen Z interprets continuous interaction as a symbol of closeness, consistency, and commitment in online friendships. Using a descriptive qualitative method, data were collected through in-depth interviews with active TikTok users who regularly maintain streaks. The findings reveal that streaks function not only as a gamified feature that motivates daily interaction but also as a form of phatic communication, maintaining social connection without necessarily conveying substantive messages. Over time, the meaning and motivation behind streaks transform from novelty and entertainment into a form of digital ritual representing emotional closeness and peer-driven social pressure. Therefore, TikTok streaks can be understood as symbolic communication practices that illustrate how Generation Z negotiates commitment, social connection, and personal balance in the era of social media.